2021
DOI: 10.1128/mra.01404-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Klebsiella pneumoniae Jumbo Phage Miami

Abstract: Bacteriophage Miami infects Klebsiella pneumoniae, a Gram-negative pathogen that is becoming an increasing threat to public health due to its multidrug resistance. Here, we describe the annotation of the 253,383-bp jumbo phage Miami genome sequence and its similarity to other myophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Annotations were attributed to 141 CDSs (shown in colour in Figure 3) leaving a total of 393 (73.6%) CDSs of unknown function. GBH019 shows high similarity to previously described jumbo phage Muenster (Mora et al, 2021), K64-1 (Pan et al, 2017) and vB_KleM-RaK2 (Sǐmoliunas et al, 2013) with DNA similarity values calculated using MASH of 98.2-98.4% but with highly dissimilar gene organisation (Supplementary Figure 1). Examination of the pangenome of these four phage using Roary 3.13 (Page et al, 2015) showed that 384 genes were common to all genomes (BLASTP > 90%).…”
Section: Jumbo Phage Gbh019supporting
confidence: 54%
See 1 more Smart Citation
“…Annotations were attributed to 141 CDSs (shown in colour in Figure 3) leaving a total of 393 (73.6%) CDSs of unknown function. GBH019 shows high similarity to previously described jumbo phage Muenster (Mora et al, 2021), K64-1 (Pan et al, 2017) and vB_KleM-RaK2 (Sǐmoliunas et al, 2013) with DNA similarity values calculated using MASH of 98.2-98.4% but with highly dissimilar gene organisation (Supplementary Figure 1). Examination of the pangenome of these four phage using Roary 3.13 (Page et al, 2015) showed that 384 genes were common to all genomes (BLASTP > 90%).…”
Section: Jumbo Phage Gbh019supporting
confidence: 54%
“…Three K51-selective phage displayed non-identical genomes of 348 kb and consequently fell into the category of jumbo (Yuan and Gao, 2017) also known as huge (Al-Shayeb et al, 2020) phage characterised by genomes of >200 kb. As isolation-based methods select against large phage (Yuan and Gao, 2017), only 94 jumbo phage have been described following isolation and only three of these, with a high degree of sequence similarity, are Klebsiella spp virions (Sǐmoliunas et al, 2013;Pan et al, 2017;Mora et al, 2021): these have genomes of 345.8 kb, making phage GBH019, GBH020 and GBH023 (Table 2) amongst the largest Klebsiella phage described and sequenced to date.…”
Section: Phage Isolationmentioning
confidence: 99%
“…S2C) in the NCBI taxonomic database. øKp_32 exhibits 95.9% nucleotide identity with Klebsiella phage Miami ( 30 ) (Fig. S2C).…”
Section: Resultsmentioning
confidence: 99%
“…Whole genome NCBI nucleotide BLAST for the bacteriophage KPN8 could not be completed due to its large size. However, many sections of its genome were found to BLAST to the previously reported novel Klebsiella jumbo phage Miami (MT701590) [41]. When analysed in a phylogenetic tree of putative capsid proteins, these two jumbo bacteriophages clustered together in a clade (Figure 2A).…”
Section: Phylogeny Of Klebsiella Bacteriophages Kpn7 and Kpn8mentioning
confidence: 94%